Fluorescence Produced by Transfection Reagents Can Be Confused with Green Fluorescent Proteins in Mammalian Cells - B. Guo; A.G. Pearce; K.E.A. Traulsen; A.C. Rintala; H. Lee (BioTechniques, 2001)
The Aequorea victoria green fluorescent protein (GFP) reporter system is a convenient way to monitor gene expression and other cellular functions in mammalian cells. To study gene expression, a GFP-fusion plasmid construct is often transfected into mammalian cells using a variety of methods including calcium phosphate- and liposome-based DNA transfer. Subsequently, the expression of GFP-fusion protein is monitored by fluorescence microscopy or flow cytometry. Here, we report that certain transfection reagents can produce fluorescence that can be detected in a wide range of wavelengths, which can be confused with GFP-fusion protein. The fluorescence false positives can be a problem, particularly when the GFP expression levels are low. To improve the GFP-based detection or screening methods, it is imperative to include an appropriate negative control and to detect GFP using a narrow-wavelength emission filter corresponding to the emission spectrum around the GFP peak.